Godinot M, Senut B, Pickford M (2018). Primitive Adapidae from Namibia sheds light on the early primate radiation in Africa. Communications of the Geological Survey of Namibia 20: 140-162. - (:unkn) unknown (My University, 2018)
The initial radiation of primates is best documented on Northern continents, in which twogroups are abundant and well-known : the Omomyiformes, often considered to be primitivehaplorhines, and the Adapiformes, usually considered to be strepsirrhines. The extinct Adapidae is oneof the families of the Adapiformes, which was first documented in Europe and more recently found inAsia and North Africa. The late Eocene African adapids, from the Egyptian Fayum deposits, appear asa group of three genera constituting with the European genus Caenopithecus, a monophyleticsubfamily, the Caenopithecinae, sister group to the otherwise exclusively European Adapinae. Wereport here the discovery, in the Middle Eocene locality of Black Crow in Namibia, of an undoubtedprimitive adapid, Namadapis interdictus nov. gen. nov. sp., which compares closely with the Europeangenus Microadapis and the Chinese genus Adapoides. It also appears smaller, more primitive, closelyrelated to the Fayum caenopithecines, being broadly ancestral to them but not directly in line with thethree genera. The three primitive middle Eocene adapid genera present in Europe, Asia and Africa leadus to recognize an early differentiation between European Adapinae and African Caenopithecinae, thelatter becoming more cristodont at smaller size than the former. A dispersal of an early adapid toAfrica is confirmed, however we suggest an Asiatic instead of a European origin for the colonizer. Thenew Namibian fossil provides clues to interpret the enigmatic Notnamaia found in the same locality :it is probably an adapid. These two forms contrast with the late early or early middle Eocene primatesrecorded in North Africa, documenting an unsuspected degree of diversity and endemism withinmiddle Eocene African primates. A new look at two poorly known late Eocene primates from thesame region in Namibia allows the recognition of a proteopithecid and emphasizes the distinctivenessof the lemuriform. In contrast with the
Keywords: African Research